Literary Theory in Indonesian English Department: between Truth and Meaning - Sarwoto, Paulus (Universitas Sanata Dharma, 2015)
Literary theory in Indonesian English Department is faced with the questions of the integrity of theory and compatibility with local context. The integrity of theory found in other social sciences is absent in literary theory since it makes use of theories of other disciplines in such a way that it departs and yet relates to those theories in a new trajectory. Ecumenical posture should be the paradigm when approaching the plurality of literary theory. The compatibility with local context has to be understood in the interconnectedness of theory in the network of global academic conversation. The decision to use or not to use certain theory should not be driven by xenophobic views or the failure to understand the complexity of theory. In this perspective, truth and meaning are never singular.Keywords: theory, ideology, humanism, literature